GAMBARAN NILAI LABORATORIUM SGOT DAN SGPT PADA PENDERITA HEPATITIS B DI RSUD ABDUL MOELOEK LAMPUNG TAHUN 2021 - Mohammad Hafizh Al Waali; Yesi Nurmalasari; Dita Fitriani; Zulfian Zulfian (Medula, 2023)
Hepatitis B is known as serum hepatitis. This disease is serious and is usually transmitted through contact with blood containing the virus. Based on the 2013 World Health Organization (WHO) report, 2 billion people in the world suffer from hepatitis, 240 million people suffer from chronic hepatitis B and 1.46 million of them die. Indonesia is a country with high endemic hepatitis B, the second largest in the South East Asian Region (SEAR) after Myanmar. The type of research used in this study is descriptive, which is a research method that shows the characteristics of the population or phenomenon being studied. The sample in this study was 95 people. The sampling method is purposive sampling technique. Univariate analysis using SPSS (Statistical Product and Service Solutions). The results of this study were that there was an increase in male sex compared to female, based on old age there was a higher increase than young age, and SGOT levels increased while SGPT was normal in patients with Hepatitis B Disease. There is a description of the normal category of SGOT value: 5-40µ/l and the value increases >40µ/l. there is a normal SGPT level value: 7-56µ/l and an increased value >56µ/l in patients with Hepatitis B at Dr. Hospital. H. Abdul Moeloek, Lampung Province in 2021..